Advances in plant and animal boron nutrition proceedings of the 3rd International Symposium on all Aspects of Plant and Animal Boron Nutrition - Xu, Fangsen. (Springer, 2007)
Boron is one of the essential micro nutrients for higher plants growth and development. Aimed at scientists, Masters or Ph D students, managers, this book reviews various aspects of boron research based on the Third International Symposium on all Aspects of Plant and Animal Boron Nutrition which was held in Wuhan, P R China in 2005.